Introducing the 'Drucebo' effect in statin therapy: a systematic review of studies comparing reported rates of statin‐associated muscle symptoms, under blinded and open‐label conditions. Issue 6 (11th October 2018) - Penson, Peter E.; Mancini, G. B. John; Toth, Peter P.; Martin, Seth S.; Watts, Gerald F.; Sahebkar, Amirhossein; Mikhailidis, Dimitri P.; Banach, Maciej; ,
Abstract: Background: The 'placebo effect' and 'nocebo effect' are phenomena whereby beneficial (placebo) or adverse (nocebo) effects result from the expectation that an inert substance will relieve or cause a particular symptom. These terms are often inappropriately applied to effects experienced on drug therapy. Quantifying the magnitude of placebo and nocebo effects in clinical trials is problematic because it requires a 'no treatment' arm. To overcome the difficulties associated with measuring the nocebo effect, and the fact that its definition refers to inert compounds, rather than drugs, we introduce the concept of 'drucebo' (a combination of DRUg and plaCEBO or noCEBO) to relate to beneficial or adverse effects of a drug, which result from expectation and are not pharmacologically caused by the drug. As an initial application of the concept, we have estimated the contribution of the drucebo effect to statin discontinuation and statin‐induced muscle symptoms by performing a systematic review of randomized controlled trial of statin therapy. Methods: This preferred reporting items for systematic reviews and meta‐analysis‐compliant systematic review was prospectively registered in PROSPERO (CRD42017082700). We searched PubMed and Cochrane Central from inception until 3 January 2018 using a search strategy designed to detect studies including the concepts (Statins AND Placebo AND muscle pain). We included studies that allowed us to quantify the drucebo effect for adverse muscle symptoms of statins by (i) comparing reported rates of muscle symptoms in blinded and unblinded phases of randomized controlled trials and (ii) comparing rates of muscle symptoms at baseline and during blinded therapy in trials that included patients with objectively confirmed statin intolerance at baseline. Extraction was performed by two researchers with disagreements settled by a third reviewer. Results: Five studies allowed the estimation of the drucebo effect. All trials demonstrated an excess of side effects under open‐label conditions. The contribution of the drucebo effect to statin‐associated muscle pain ranged between 38% and 78%. The heterogeneity of study methods, outcomes, and reporting did not allow for quantitative synthesis (meta‐analysis) of the results. Conclusions: The drucebo effect may be useful in evaluating the safety and efficacy of medicines. Diagnosis of the drucebo effect in patients presenting with statin intolerance will allow restoration of life‐prolonging lipid‐lowering therapy. Our study was limited by heterogeneity of included studies and lack of access to individual patient data. Further studies are necessary to better understand risk factors for and clinical management of the drucebo effect.